Efficacy of Oregano Extract Ointment on Fibroblast Cells and Epidermis in Albino Rats with Excisional Wound Model - Lesmana, Muhammad Arfan; Amri, Indah Amalia; Cahyanissa, Ardilla Rachma; Geoputri, Kartika Myrnandari; Anisa, Agri Kaltaria; Hardian, Andreas Bandang (Jurnal Medik Veteriner, 2023)
This study aimed to determine the effect of oregano extract ointment therapy on the number of fibroblast cells and the epidermal thickness in excised wounds. The experimental animals used were 20 male Wistar strain albino rats, 12 weeks old, weighing 100–150 g, divided into 5 treatment groups i.e., (C-) not excised and without ointment, (C+) excised and without ointment, and the treatment group were excised using a 5 x 5 mm biopsy punch and treated with oregano extract ointment using concentrations of (T1) 3%, (T2) 6% and (T3) 9% twice daily for 14 days in an excised wound. The variables observed in this study were the number of fibroblast cells and the epidermal thickness by the HE staining method then measured using ImageJ. Data analysis used the One-Way ANOVA test followed by the Tukey test (p < 0,05). The results showed a decrease in the number of fibroblast cells and an increase in the epidermal thickness in the 6% concentration ointment. This study concluded that the administration of oregano extract ointment with a concentration of 6% was the optimal concentration in accelerating the final proliferative phase, characterized by a decrease in fibroblast cells and an increase in epidermal thickness.